Role of FNAC in the Diagnosis of Cervical Lymphadenopathy - C. Bhavani; Neeraja M.; K.P.V. Varalakshmi; P.V. Ramana Babu; B. Chaitanya; P. Sravani (International Journal of Medical Research and Review, 2014)
Background: Cervical lymphadenopathy is one of the commonest presentations in inflammatory and neoplastic disorders. Fine Needle Aspiration Cytology (FNAC) is simple, quick, inexpensive and minimally invasive OPD technique used for establishing the etiology of cervical lymphadenopathy. In this study we describe cytomorphological patterns of FNAC of cervical lymph nodes and it’s utility in establishing diagnosis.Aims & Objectives: (1) To assess the distribution of various cytomorphological patterns of cervical lymphadenopathy; (2) To assess the age specific distribution of various cytomorphological patterns of cervical lymphadenopathy.Materials and Methods: This study was carried out at Government Medical College and Hospital, Anantapuramu, on 265 clinically diagnosed cases of cervical lymphadenopathy over a period of three years from July 2011 to June 2014. Fine Needle Aspiration Diagnosis was correlated with details of relevant clinical findings and investigations.Results: Total 265 cases were studied, out of these 232 (87.55%) were found inflammatory and 33 (12.45%) were neoplastic. Tuberculosis was the most common disease found in 112 (42.26%) patients followed by reactive nonspecific lymphadenitis in 94 patients (35.47%), Metastatic tumours 30 patients (11.32%), suppurative lymphadenitis 26 patients (9.8%), Lymphoma 3 (1.13%). Highest incidence of cervical lymphadenopathy was found in patients of 21 to 40 years age group.Conclusion: Fine Needle Aspiration Cytology is easy, simple, safe, reliable and non-invasive procedure for diagnosis of cervical lymphadenopathy.